Pengembangan Bahan Ajar Berbasis Video Animasi Materi Sholat Berjamaah Untuk Meningkatkan Motivasi Belajar Siswa - Nur Aisah Rahmah; Jasiah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Teaching materials are a key element in optimizing the learning process. Learning video-based teaching materials commonly used in the learning process have a relevant impact. The most important thing is to arouse the spirit of learning and motivation of the students themselves. The purpose of this research is to develop and test the effectiveness of video-based teaching materials to increase student learning motivation in Blessing Integrated 7th grade. The research method used is Research and Development (R&D) which uses data collection techniques of observation, interview and learning motivation questionnaire. The results of the study showed that when the video teaching materials were applied, one expert gave an average score of 4 points in the “appropriate” category. The results of the article show that the expert gave an average score of 4 with the appropriate category. The results showed that 93,3% of students were very satisfied with using videos in the learning process. These results indicate that the video-based learning materials introduced in Fiqh learning are considered feasible to develop as one of the alternative methods to increase student learning motivation.